Meningkatkan Kemampuan Literasi dan Kreativitas Siswa di UPT SD Negeri 060815 Melalui Program Kampus Mengajar - Panjaitan, Sirana Mikelvania Baby; Atika, Tuti (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Education is one thing that is quite essential for humans. As long as humans are alive, humans will continue to learn. The state itself has prepared formal education for its citizens. This is aimed at equal distribution of education throughout Indonesia so that Indonesian people can live independently in society and can continue their education to a higher level. The problem of literacy and creativity are two things that need attention because currently, the interest in literacy and creativity of students is getting lower. Even though by having these two things students empower themselves and improve their quality as individuals. Through the Merdeka Belajar Kampus Merdeka (MBKM) Kampus Mengajar program, the authors designed and implemented a learning program to improves students' literacy abilities and interests and increase student creativity which applied at UPT SD Negeri 060815 Medan City. The implementation of this program uses the social group work method to find out the progress of students, including (1) Preparation, (2) Intake and contract, (3) Assessment, (4) Planning, (5) Intervention, (6) Evaluation, and (7) Termination.